The analysis of wear intensity of lubricated and unlubricated locomotive wheel sets flanges - Mikaliūnas, Šarūnas; Lingaitis, Leonas P.; Vaičiūnas, Gediminas (Transport, 2004)
The wear dynamics of wheel ‐ set tyres of diesel locomotives was investigated. Basing on research results it is possible to predict wheel‐tyre safety margin, to improve maintenance and to state the periodicity of repair, as well as most efficiently to use traction rolling‐stock repair funds.First Published Online: 27 Oct 2010